Anticoagulation in adults with congenital heart disease: The who, the when and the how?. Issue 6 (3rd October 2014) - Jensen, A S; Idorn, L; Nørager, B; Vejlstrup, N; Sondergaard, L
Abstract : Adults with congenital heart disease are a growing population. One of the major challenges in the care of these patients is to prevent thromboembolic episodes. Despite relative young age and no typical cardiovascular risk factors, this cohort has a high prevalence of thrombotic events. It is difficult to use treatment algorithms from the general adult population with acquired heart disease in this heterogeneous population due to special conditions such as myocardial scarring after previous surgery, atypical atrial flutter, prothrombotic conditions and the presence of interatrial shunts. Furthermore, there is a lack of scientific evidence regarding how to prevent thromboembolic events with anticoagulation in adults with congenital heart disease. The aim of this paper is to review the current literature pertaining to anticoagulation in adults with congenital heart disease and hence enable recommendations for which patients are likely to benefit from which anticoagulation treatments, when they should be considered and how these would be carried out.